Considerations on the paradox of perception in Bergson - Rodrigues, Paulo César [UNESP] (UNISINOS - Universidade do Vale do Rio Dos Sinos, 2018)
The present article approaches Bergson’s theory of perception in terms of its ambiguous or paradoxical aspects. More precisely, it intends to examine the problem of perception as “virtual action” and, at the same time, as insertion into the being of matter, that is, into a reality in which there are only “real actions”. By establishing a distinction between levels of argumentation in the philosopher’s text, that is, between a methodological level and an ontological level, the article seeks to solve the difficulties found in Bergson’s theory of perception. For this purpose, it is necessary to discuss the author’s metaphysical theses, his metaphysics of memory.
Considerações sobre o paradoxo da percepção em Bergson1
Keywords: Bergson; Perception; Real; Virtual